The Role of Innovation Culture as a Leadership Effort in Improving Adaptive Performance: A Mediation and Moderated Model - Srimulyani, Veronika Agustini; Ellitan, Lena; Hermanto, Yustinus Budi (Journal of Ecohumanism, 2025)
Micro-foundation in dynamic capabilities refers to the most basic level or elements that form an organization's ability to adapt and change in the face of a dynamic organizational environment. The variables examined in this study are flexible leadership, innovation culture, workplace spirituality, and adaptive performance. This study was conducted at a secondary school owned by a Foundation (private) in East Java Province, Indonesia, with a sample of 100 school leaders accredited A. This study uses the Partial Least Square Structural Equation Modelling (PLS-SEM) statistical technique using the Smart PLS program as an analysis tool. The results of the hypothesis testing revealed that: 1) Flexible leadership significantly increases innovation culture; 2) Innovation culture significantly increases adaptive performance; 3) Innovation culture acts as a full mediation of the positive impact of flexible leadership on adaptive performance; 4) Workplace spirituality strengthens the positive impact of innovation culture on adaptive performance. These findings reveal the important role of innovation culture in encouraging leaders and subordinates to think creatively, take risks, and develop new ideas so as to increase adaptive performance which in turn contributes to improving overall organizational performance. Innovation culture can be enhanced through flexible leadership practices and strengthening workplace spirituality in daily work life.